Career talk: specialist nutrition nurses. (2nd November 2021) - Santos, Sara; Smyth, Edel; Barbaso, Iris
Abstract : In this interview, part of a series about the career pathways of experienced gastrointestinal specialists, Sara Santos speaks with Edel Smyth and Iris Barbaso